The neurobiology of plant-based therapeutics in women's reproductive health: mechanisms, efficacy, and clinical translation - Liu, Xue; Bin, Chengli; Zhou, Zehui; Zeng, Tongtong; Wu, Kun; Luo, Yiping; Liu, Qun; Wei, Shaobin (Frontiers in Nutrition, 2025)
This review examines the neurobiological mechanisms by which plant-derived compounds influence women's reproductive health through the neuroendocrine-reproductive axis. Gynecological disorders frequently present with neurological manifestations, including cognitive decline in perimenopause, anxiety and depression in polycystic ovary syndrome (PCOS), and central sensitization in endometriosis. Bioactive compounds from medicinal plants, including polyphenols and phytoestrogens, demonstrate therapeutic potential through their anti-inflammatory, antioxidant, and neuromodulatory properties. These multi-target compounds offer advantages over conventional single-target therapies by simultaneously regulating multiple physiological processes. The review explores applications in specific gynecological conditions and discusses the development of dietary supplements and functional foods incorporating these plant-derived ingredients. The growing market for these products presents opportunities for innovative formulations with enhanced bioavailability and personalized approaches. Future research directions include integrating neuroimaging with herbal research, improving clinical translation, and establishing regulatory frameworks for the global application of these plant-derived interventions to enhance female neuroendocrine-reproductive health.